A PROSPECTIVE SINGLE-BLINDED STUDY ON THE SAFETY AND EFFICACY OF ZINC SUPPLEMENTATION IN PULMONARY TUBERCULOSIS - B, Yeswanth Prasanna Kumar; D, Praveen; M, Vijey Aanandhi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Aim and Objectives: The aim of the study was to study the serum zinc (Zn) levels, safety, and efficacy of Zn supplementation in pulmonary tuberculosis (PTB) patients. Methods: A randomized single-blinded study of two groups: Group A received conventional TB therapy while Group B received conventional TB therapy along with 15 mg of Zn tablet. 40 patients were assigned in each group by randomized permuted blocks. Results: After 8 weeks of treatment in Group A 27 patients and Group B 36 patients were found to be sputum negative with p=0.0421 and 0.0629. After 24 weeks of treatment in Group A 37 patients and Group B 40 patients were found to be sputum negative with p=0.00976 and 0.00971. By this, the given treatment was effective in the patients with PTB. Conclusion: Zn supplementation improves the effect of TB medication treatment and results in earlier sputum smear conversion.